Cell-free DNA and tumor exosome cargo as diagnostic and prognostic marker for prostate cancer - Temilola, Dada (Department of Integrative Biomedical Sciences (IBMS), 2023)
According to the Global Cancer Statistics 2020, prostate cancer (PCa) is the second most commonly diagnosed male cancer and second leading cause of cancer death among men globally. Prostate cancer is known to be more aggressive among men of African origin with reasons not fully known. Previous studies have revealed PCa to be of a serious disease burden among African populations with PCa being the major cause of male cancer mortality. Prostate specific antigen (PSA) has long been introduced as a biomarker for screening in PCa diagnosis. However, serum PSA has low sensitivity for PCa diagnosis which has led to serious harm such as overdiagnosis and other complications of treatment for indolent disease. This makes it imperative to search for other novel biomarkers with high sensitivity and specificity for early diagnosis and management of prostate cancer. This study was aimed to characterize plasma and urinary cfDNA and tumour exosome cargo as diagnostic biomarker for PCa in South African populations with the goal of discovery of reliable, non-invasive, and novel biomarkers of PCa. We performed miRNA sequencing of exosomal RNA extracted from high and low Gleason's score PCa plasma samples. We performed differential expression (DE) of TCGA data and exosomal miRNA data and which we identified 185 miRNA and 65 miRNAs respectively. A comparison of the differential expressed TCGA miRNA and exosomal miRNA showed 13 miRNAs common between the two data with 7 of the 13 miRNAs expressed in the same direction. We further validated the expression of the 7 miRNAs using real time PCR in exosomal miRNA of high and low Gleason's score PCa samples and benign prostatic hyperplasia (BPH). We also performed whole exome sequencing of urinary cell free DNA and we identified 31 mutated genes. We reported for the first time an association between 27 of these genes and PCa in African populations. Four of the genes have earlier been identified as promising biomarker for prostate cancer diagnosis among African men. We also performed real time PCR quantification of cell free DNA to determine the concentration and DNA integrity of cfDNA in PCa and BPH of plasma and urine samples and which we were able to identify significantly higher plasma cfDNA level in PCa than BPH samples. We identified herein putative diagnostic biomarkers in plasma and urinary cfDNA and exosomes cargo for diagnosis of PCa in South African populations.